2020
DOI: 10.3390/ijms21239171
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Lipoaspirate and Adipose Tissue-Derived Stem Cells Contact Culture on Breast Cancer Cells: Implications in Breast Reconstruction

Abstract: Background: Autologous fat transfer in the form of lipoaspirates for the reconstruction of the breast after breast cancer surgery is a commonly used procedure in plastic surgery. However, concerns regarding the oncologic risk of nutrient-rich fat tissue are widely debated. Previous studies have primarily focused on studying the interaction between adipose-derived stem cells (ASCs) and breast cancer cells. Methods: In this study, we performed a comprehensive analysis of the paracrine- and contact-based interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
(72 reference statements)
0
18
0
1
Order By: Relevance
“…Ongoing studies include investigations into the secretory function of adipocytes as well as tumor cells and the role of lipid metabolism and specific ECM components in tumor cell proliferation and migration, also using modified hydrogel formulations that support migration of the tumor cells. Furthermore, due to its modular design and the possible long-term culture, the presented model may also be utilized to investigate the interaction of ASC-enriched lipografts and breast cancer cells in the context of breast reconstruction in an in vivo-like 3D environment, which is an important aspect to evaluate this treatment in terms of oncological risk [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ongoing studies include investigations into the secretory function of adipocytes as well as tumor cells and the role of lipid metabolism and specific ECM components in tumor cell proliferation and migration, also using modified hydrogel formulations that support migration of the tumor cells. Furthermore, due to its modular design and the possible long-term culture, the presented model may also be utilized to investigate the interaction of ASC-enriched lipografts and breast cancer cells in the context of breast reconstruction in an in vivo-like 3D environment, which is an important aspect to evaluate this treatment in terms of oncological risk [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among all these clinical trials, no evidence of a potential pro-oncogenic role of ADSCs has been shown despite pre-clinical studies that raised some evidence that adipose stem cells might have a role in the tumor microenvironment as well as in tumor promotion [ 132 , 133 , 134 ]. A recent report demonstrated that human lipoaspirate material had no pro-oncogenic properties in vitro [ 135 ]. However, long term in vivo experiments and follow-up of treated patients are still needed.…”
Section: Properties Of Adscs and Their Clinical Applicationmentioning
confidence: 99%
“…However, in a recent study carried out by Ejaz et al, (2020), it was found that lipoaspirates and ADSCs did not increase the proliferation rate of breast cancer cells either through paracrine- or contact-dependent interactions [ 33 ]. They stated that a previous study on the effect of ADSCs in increasing tumor progression using co-culturing or an In-vivomodel method was inconsistent with the clinical scenario based on the injection of intact adipose parcels into a large tissue bed for breast reconstruction.…”
Section: Part Ii—the Trick: Side Effect Of Treatment Using Adscsmentioning
confidence: 99%
“…They stated that a previous study on the effect of ADSCs in increasing tumor progression using co-culturing or an In-vivomodel method was inconsistent with the clinical scenario based on the injection of intact adipose parcels into a large tissue bed for breast reconstruction. Since most of the studies on this topic relied on In-vitro differentiated adipocytes or paracrine interactions between cells as experimental models, Ejaz et al, (2020) used a clinically relevant animal model and reported no increase in tumor size, proliferation, histological grade, or metastatic spread [ 33 ]. Even though their result contrasted with the conclusion of a previous study by Koellenspergers et al, (2017), its positive outcome might become something that scientists could build on in the future to create novel breast cancer treatments.…”
Section: Part Ii—the Trick: Side Effect Of Treatment Using Adscsmentioning
confidence: 99%